Online social networking and subjective well-being: Mediating effects of envy and fatigue. (October 2019) - Zhou, Mingming; Zhang, Xiaotian
Abstract: The primary goal in this exploratory study is to test the theoretical relationships between social networking tools (i.e., Wechat), envy, fatigue and emerging adults' well-being. We conducted a survey of 503 Chinese university students who are regular Wechat users. Using structural equation modeling, we found that the extensive use of Wechat had both direct and indirect effects on their well-being and that the association between Wechat use and subjective well-being was mediated by envy. These findings contribute to our understanding of the mechanisms through which the use of online social networking tools is related to subjective well-being and suggest the need to attend to the psychological consequences of the extensive use of social networking tools. Highlights: This study investigated the effects of social networking tools on well-being. Extensive use of Wechat had both direct and indirect effects on their well-being. The association between Wechat use and subjective well-being was mediated by envy, but not fatigue.